Pengaruh Harga Promosi Dan Kualitas Pelayanan Terhadap Konsumen Pada Mini Market Al-Khaibar ( Studi Kasus Pada Mahasiswa FEB Universitas Islam Malang Yang Berbelanja di Al-khaibar) - Robiatul Adawiyah; Muhammad Ridwan Basalamah; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This research was conducted at Mini Market Al-Khaibar Jl. Solar system. The type of research used is a quantitative approach. The purpose of this study was to determine the effect of price, promotion and service quality, on consumer satisfaction with the Al-Khaibar Mini Market. The independent variables used are price, promotion and service quality, while the dependent variable is customer satisfaction. The sample used in this study was 91 respondents who were students of the Islamic University of Malang class 2018. The data collection technique used a questionnaire. The analytical method used is instrument test, multiple linear regression analysis, classical assumption test, f test, t test and determination test using SPSS computer software for data processing. The results of this study indicate that price affects consumer satisfaction, promotion affects consumer satisfaction and service quality affects consumer satisfaction and simultaneously price, promotion and service quality affect consumer satisfaction. Keywords: Price, Promotion and Service Quality on Consumer Satisfaction